Crystal structure and Hirshfeld surface analysis of (E)-2,4-di-tert-butyl-6-[(3-chloro-4-methylphenylimino)methyl]phenol - Kansiz, Sevgi (Acta Crystallogr E Crystallogr Commun, 2018)
The title Schiff base compound, C(22)H(28)ClNO, shows mirror symmetry with all its non-H atoms, except the tert-butyl groups, located on the mirror plane. There is an intramolecular O—H⋯N hydrogen bond present forming an S(6) ring motif. In the crystal, the molecules are connected by C—H⋯π interactions, generating a three-dimensional supramolecular structure. Hirshfeld surface analysis and two dimensional fingerprint plots were used to analyse the intermolecular interactions present in the crystal, indicating that the most important contributions for the crystal packing are from H⋯H (68.9%) and C⋯H/H⋯C (11.7%) interactions.